Pengaruh Produk dan Proses Terhadap Keputusan Pembelian pada E-Commerce di Kecamatan Tanjung Batu - Anis Zahira; Nadia Afrilliana (CV. Doki Course and Training, 2026)
This study aims to determine 1. The Influence of Products and Processes on Purchasing Decisions on Bukalapak E-Commerce in Tanjung Batu District, Ogan Ilir Regency. 2. The Influence of Products on Purchasing Decisions on Bukalapak E-Commerce in Tanjung Batu District, Ogan Ilir Regency. 3. The Influence of Processes on Purchasing Decisions on Bukalapak E-Commerce in Tanjung Batu District, Ogan Ilir Regency. This type of research is Associative, using the variables Purchase Decision (Y), Product (X1), and Process (X2). The number of samples in this study was 100 respondents taken by Purposive Sampling. The data used are primary and secondary data with data collection methods using questionnaires. The analysis techniques used are Multiple Linear Regression Analysis, F Test and t Test, and Coefficient of Determination. The results of the f test together show that Products and Processes simultaneously have a significant influence on Purchasing Decisions on Bukalapak e-commerce in Tanjung Batu District, Ogan Ilir Regency. Meanwhile, in the partial t-test, Product has a significant influence on Purchasing Decisions, and Process has a significant influence on Purchasing Decisions.